Some Things Are Better Unknown: Confronting Traditional Practices of Prophecy in African Cultural Beliefs through Ola Rotimi's The Gods Are Not to Blame - OLAWE, Opeyemi Emmanuel; ADEGITE, Adekunle; BABALOLA, Olaide Morayo; ADEOSUN, Dunsin Oyindamola (Universitas Sanata Dharma, 2024)
In contemporary Nigeria, the proliferation of prophetic claims has profoundly influenced popular religious practices across all societal strata. This phenomenon engages individuals from various backgrounds as they seek divine insights and prophecies from spiritual leaders. This study focuses on Ola Rotimi's play The Gods Are Not to Blame to critically examine the role of prophecy within African cultural beliefs. While existing scholarship on Rotimi's work often analyzes themes of fate, tragedy, and the allocation of blame within the play among others, scant attention has been paid to the fundamental role of prophecy itself as the root cause of the play’s tragic events. This research aims to conduct a deconstructive reading of the play, scrutinizing how the characters' pursuit of foreknowledge and attempts to alter their fates paradoxically precipitate their destinies. The method involves a detailed textual analysis of the play, focusing on key dialogues and actions that highlight the characters' motivations and the unfolding of events. The findings reveal two key instances: first, Baba Fakunle’s prophecy, which foretells disaster for Odewale’s family, leads his parents to attempt to kill him to prevent the predicted calamity. Ironically, this attempt to alter the future sets in motion the very disaster they sought to avoid. Secondly, an elder’s parable causes Odewale to discover the prophecy's truth. In trying to understand and avoid his destiny, Odewale discovers that his actions to prevent it end up fulfilling it. Both instances suggest that the desire to know and change the future is fraught with peril, often precipitating the very outcomes one seeks to avoid. The conclusion emphasizes the prudence of embracing the uncertainty of the future, as attempting to alter it can lead to unintended and often tragic consequences.